Implementation of Daily Performance Monitoring in Improving Moral Education - Rohmi Suminar Wahyuningsih; Mohd Yasin bin Mohd Amin; Katni; Aldo Redho Syam (NAJAHA, 2025)
This article aims to describe the implementation of daily performance monitoring in improving Adab education at Azmania Islamic Boarding School in Ponorogo. The research design used in this study is descriptive qualitative research. Data collection techniques include observation, interviews, and documentation, while data analysis techniques use data analysis and Miles and Huberman's model, including data reduction, data display, and conclusion drawing. The research findings show that the role of daily performance monitoring in implementing Adab education is crucial. It helps teachers to monitor, evaluate, and make policies to improve the Adab education system. Furthermore, the Adab education at Azmania Islamic Boarding School has improved over time, from initially not understanding daily Adab to being able to implement it well. The implementation is carried out through three stages of the method, namely exemplary behavior, habituation, and knowledge insight.